2020
DOI: 10.1109/access.2020.3034489
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Measurement of Particulate Matter Concentrations on Urban Streets: System Development and Field Verification

Abstract: The authors would like to thank the members of their research team for their valuable suggestions and contributions to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This is greatly facilitated by the portability, ease to deploy, and low energy consumption of low-cost sensors, which offers great flexibility in the study design. Instrument miniaturization and cost reduction have allowed studies to comprehensively map air quality by deploying such devices on transport modes such as trash trucks, taxi fleets, and trams. ,, We notice a significant increase in studies carried out by bikes and persons, which brings a unique opportunity to assess personal exposure at unprecedented temporal and spatial resolutions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is greatly facilitated by the portability, ease to deploy, and low energy consumption of low-cost sensors, which offers great flexibility in the study design. Instrument miniaturization and cost reduction have allowed studies to comprehensively map air quality by deploying such devices on transport modes such as trash trucks, taxi fleets, and trams. ,, We notice a significant increase in studies carried out by bikes and persons, which brings a unique opportunity to assess personal exposure at unprecedented temporal and spatial resolutions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Study [42] demonstrated the feasibility of high-resolution spatial and temporal analysis of particle concentrations in urban areas using mobile setups. Results comparable to fixed station network values, offering insights into PNC and particle concentration variability.…”
Section: Related Workmentioning
confidence: 96%
“…In addition, nitrogen dioxide is very harmful for human because it belongs to the second type of danger. According to statistic data, traffic pollution in large cities is from 70 to 90 percent among all pollution [6][7][8][9]. Therefore, monitoring of this substance is a very relevant topic [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%